Development of low cost mixed metal oxide based diesel oxidation catalysts and their comparative performance evaluation. Issue 61 (13th June 2016) - Shukla, Pravesh Chandra; Gupta, Tarun; Labhsetwar, Nitin Kumar; Agarwal, Avinash Kumar
Abstract : A four cylinder diesel engine was used to evaluate the performance of two non-noble metal based diesel oxidation catalysts for emission parameters such as particulate mass, elemental/organic carbon (EC/OC), and trace-metal content in particulates. Abstract : A four cylinder transportation diesel engine was used to evaluate the performance of two non-noble metal based diesel oxidation catalysts (DOC) with respect to various emission parameters such as particulate mass, elemental/organic carbon (EC/OC) content, and trace-metal content in particulates. Two new non-noble metal based DOCs were prepared and evaluated using mixed oxide (Co3 O4 –CeO2 ) and perovskite catalysts with ceria support. Emissions were evaluated before and after the use of a commercial DOC for comparison. Experimental results showed that newly prepared DOCs were effective in reducing the organic carbon content of particulates. The effectiveness of these DOCs increased with higher engine loads. Performance of these two prepared DOCs was comparable to the commercial DOC. Trace metal concentration in particulates increased for most metals detected, primarily due to reduced organic carbon content of particulates emitted from the DOC. Prepared DOCs showed significant reduction in organic carbon at 50% and higher engine loads. Significant organic carbon reduction was found to be responsible for particulate reduction.